Interpretation of the Knowledge System as a Historical Development of the "Concept" based on the Preface of the Phenomenology of the Spirit - Mostafa Abedi jige (حکمت و فلسفه, 2023)
IntroductionThe fundamental problem that has always been paid attention to in the history of thought is that 1- What is the relationship between subject and object? 2- How can we pass from subject to object and know the internal structure of the objective world? The answer to this epistemological problem in the modern period caused extensive changes in the system of thought, and out of it came rationalism, empiricism, and idealism. To explain the mentioned ratio, some like the materialists put the principle as a material object and consider everything, especially the knowledge system, to be explainable based on it. On the other hand, subjective idealism puts the subject first instead of emphasizing the object and bases the explanation of the empirical world on the concept in Kant and rational intuition in Fichte. In both of them, the knowledge system was based on a hard ground that made knowledge as a whole possible by transcending the knowledge system itself. But Hegel took on a completely different role in the Phenomenology of Spirit. 1. by considering the concept as fundamental in the knowledge system, 2. giving it an ontological aspect due to its connection with the object-in-itself, 3. making it fluid from the stage of abstract substance to the stage of the actual subject, he introduced the concept as the absolute with its movement from the potential stage to the actual stage, it determines the subject and the object and harmonizes existence and thought as a system and a dialectical whole. With this work, Hegel was able to rule out elitism in the system of science, and by knowing the concept and its connection with the absolute as fundamental, he reconciled the absolute knowledge with the conventional view and revealed it to everyone. In this article, the author tries to present a concrete interpretation of the system of knowledge in Hegel's thought by focusing on the "concept" according to the preface of the phenomenology of the soul. For this purpose, the author deals with the position of the concept and the explanation of its structure in the phenomenology of the soul under the following nine titles: the position of the concept in the phenomenology of the soul; prior concepts and the beginning of the phenomenology of the soul from essence as nothing; Hegel's critical stance towards instrumentalization of consciousness; the concept and passing from the phenomenal field to the realm of the object in itself; the concept in motion, the ontological foundation of the world; Hegel and the two-way reflection of thought and existence; experience and its extension to the object itself; Hegel's criticism of elitism in the knowledge system through the negation of rational intuition; Hegel's system of knowledge is the only way for subjective idealism to escape from skepticism.ConclusionIn short, Hegel is trying to define existence and knowledge as a system through a concrete understanding of the concept and its historical and existential development and make thought and existence compatible with each other. In order to turn the knowledge system into something concrete, Hegel changes the foundation of science from fixed transcendental matters to a mediated and negative concept by negating prior concepts and intellectual intuition. In this view, instead of starting from prior and fixed things, which is the condition of knowledge of the concept of the world, science starts from a concept that is considered empty and abstract in the first stage. In this way, knowledge does not start from a definite and actual matter, but from a concept whose only determination is the power and ability to become absolute. According to Hegel, it is this concept that, through its inner negation, dismantles each particle of its former world after another particle and silently matures in a new form. With this statement, Hegel negates any first fixed point that is outside the movement of the concept and conceptual knowledge is based on it, and in this way, everything is determined and known within the concept in motion. This is where Hegel finds the ability to eliminate any dark spots in the history of consciousness and by clarifying the absolute for everyone, destroys the foundation of elitism that Fichte and Schelling's rational intuitions emphasized. Also, by ontologicalizing the concept and relating it to the object-in-itself, Hegel escapes from the skepticism that plagues mental idealism to escape from skepticism.